The yin and yang of intracellular delivery of amphipathic optical probes using n-butyl charge masking. Issue 17 (3rd February 2022) - Agarwal, Hitesh K.; Janicek, Radoslav; Zhao, Jun; Sambath, Karthik; Egger, Marcel; Niggli, Ernst; Ellis-Davies, Graham C. R.
Abstract : The size of the caging chromophore conditions the ability of intracellular cargo delivery and esterase charge unmasking. Abstract : Monitoring and manipulation of ionized intracellular calcium concentrations within intact, living cells using optical probes with organic chromophores is a core method for cell physiology. Since all these probes have multiple negative charges, they must be smuggled through the plasma membrane in a transiently neutral form, with intracellular esterases used to deprotect the masked anions. Here we explore the ability of the synthetically easily accessible n -butyl ester protecting group to deliver amphipathic cargoes to the cytosol. We show that the size of the caging chromophore conditions the ability of intracellular probe delivery and esterase charge unmasking.